Edinburgh 2010 : Mission then and Now - Kerr, David A.; Ross, Kenneth R.; World Missionary Conference (2010 : Edinburgh, Scotland); World Missionary Conference (1910 : Edinburgh, Scotland) (Oxford : Regnum, 2009)
"The Centenary of the World Missionary Conference, held in Edinburgh 1910, is a suggestive moment for many people seeking direction for Christian mission in the 21st century. Several different constituencies within World Christianity are holding significant events around 2010. Since 2005 an international group has worked collaboratively to develop an interncontinental and multidenominational project, now known as Edinburgh 2010, and based at New College, University of Edinburgh. This initiative brings together representatives of twenty different global Christian bodies, representing all major Christian denominations and confessions and many different strands of mission and church life, to prepare for the Centenary." (Daryl Balia, International Director Edinburgh 2010).
Foreword -- Preface -- Acknowledgements -- In memoriam -- The Edinburgh 1910 World Missionary conference : its eight commissions in historical context and their continuing significance / David A. Kerr, Kenneth R. Ross -- Commission one : carrying the gospel to all the non-Christian world : the commission in summary -- Commission One and the church's transforming century / Andrew F. Walls -- Commission One after a century of violence : the search for a larger Christ / Kosuke Koyama -- Commission two : the church in the mission field : the commission in summary -- The church in the mission field : a Nigerian/African response / Teresa Okure -- From mission to church and beyond : the metamorphosis of post-Edinburgh Christianity / Kyo-Seong Ahn -- Commission three : education in relation to the Christianization of national life : the commission in summary -- To hang a ladder in the air : an African assessment / Ogbu U. Kalu -- Missionary education : an ambiguous legacy / M.P. Joseph -- Commission four : the missionary message in relation to the non-Christian religions : the commission in summary -- Adventures in Christian-Muslim encounters since 1910 / Gulnar Francis-Dehqani -- A world of religions and a gospel of transformation / Vinoth Ramachandra -- Commission five : the preparation of missionaries : the commission in summary -- Changing images in the formation for mission : Commission five in light of current challenges : a western perspective / Anne-Marie Kool -- Commission six : the home base of missions : the commission in summary -- Mission from everywhere to everyone : the home base in a new century / Samuel Escobar -- Commission seven : missions and governments : the commission in summary -- Christian mission and political power : Commission seven revisited / Tinyiko Maluleke -- Commission seven in light of a century of experience in Cuba / Adolfo Ham -- Commission eight : cooperation and the promotion of unity : the commission in summary -- Cooperation and the promotion of unity : a World Council of Churches perspective / Samuel Kobia -- Cooperation and the promotion of unity : an evangelical perspective / Rosemary Dowsett -- Cooperation and the promotion of unity : an Orthodox perspective / Viorel Ionita -- Cooperation and the promotion of unity : a Roman Catholic perspective / John Radano -- Cooperation and the promotion of unity : a Pentecostal perspective / Cecil M. Robeck, Jr. -- The commissions after a century / Kenneth R. Ross, David A. Kerr.
Includes bibliographical references (pages 319-335) and index.
Keywords: Missions -- Theory -- History -- 20th century; Missions -- Theory -- History -- 21st century; Missions -- History -- Congresses; Missions -- Theory -- Congresses; Missions and Christian union -- Congresses; Conference papers and proceedings; History; Conference papers and proceedings